Finance and Growth: A Survey of the Theoretical and Empirical Literature - Felix Eschenbach (Tinbergen Institute, 2004)
This paper reviews the theoretical and empirical literature on links between domestic financial development and economic growth. It starts with the pioneers in this field and then classifies two main schools favouring liberal financial regimes. First McKinnon and Shaw advocated financial liberalization in a period of widespread government intervention in credit markets. After that a period of criticism of free market regimes followed, partly based on unsuccessful policies. The literature on financial development and endogenous growth pushed the discussion back into the direction initially advocated by McKinnon and Shaw. We review a huge body of empirical literature, which generally finds positive associations between domestic financial development and economic growth. The evidence suggests, however, enormous heterogeneity across countries, regions, financial factors, and directions of causality.
Keywords: E44; G21; O16; 330; Financial Liberalization; Financial Development; Endogenous Growth; Finanzmarkt; Finanzmarktregulierung; Wirtschaftswachstum